Reference ranges for the fetal cardiac circumference derived by cardio-spatiotemporal image correlation From 14 to 40 weeks' gestation - Traisrisilp K. (2017)
Objectives-The purpose of this study was to construct reference ranges for the fetal cardiac circumference derived from volume data sets obtained by cardio-spatiotemporal image correlation. Methods-A prospective descriptive study was conducted on normal singleton pregnancies with certain dates from 14 to 40 weeks' gestation. All underwent cardio- spatiotemporal image correlation to acquire volume data sets for subsequent analysis. Cardiac circumferences were measured offline in a multiplanar view with 4-dimensional imaging software. The reference ranges were constructed against gestational weeks and the biparietal diameter as independent variables, using regression models for both the mean and SD. Results-A total of 678 satisfactory volumes were analyzed. Normal reference ranges for predicting means and SDs of the fetal cardiac circumference were established based on best-fitted equations. The mean cardiac circumference (millimeters) was modeled as a function of gestational age (weeks) and biparietal diameter (centimeters) as follows: cardiac circumference = -53.11 + 6.56 × gestational age - 0.035 × gestational age 2 (SD = 0.67 + 0.18 × gestational age) and -17.60 + 17.68 × biparietal diameter (SD = 1.651 + 0.61 × biparietal diameter). Equations for z score calculation were also provided, and percentile charts for predicting the cardiac circumference at various points of gestational age and biparietal diameter were constructed. Conclusions-Normal reference ranges and z scores for the fetal cardiac circumference have been provided. These normative data may be useful tools for assessment of fetal cardiac size, especially in cardiomegaly due to fetal anemia. © 2011 by the American Institute of Ultrasound in Medicine.